Walenty Hieronim Julian Kamocki (1858–1923) - Grzybowski, Andrzej; Kazało, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Walenty Kamocki (1858–1923) was a Polish ophthalmologist, the chief physician at the Institute of Ophthalmology in Warsaw. His major fields of interest were histology, embryology and pathomorphology. He described pathological lesions within the iris pigment epithelium in diabetes. His other works concerned conjunctival degeneration, cataract surgery, retinal detachment, eyelid reconstructive surgery as well as ophthalmic pharmacology and oncology. He was a social activist as a member of many organisations and scientific societies. He was awarded the Order of Polonia Restituta and the Grand Cross of the National Order of the Legion of Honour.